Development of a method for rapid detection of fires based on combined current sampling and dispersions of a controlled hazardous environmental parameter - Pospelov, Boris; Rybka, Evgeniy; Otrosh, Yurii; Maladyka, Larysa; Krainiukov, Olekcii; Kurtseitov, Tymur; Vorovka, Marharyta; Hryshko, Svitlana; Pidhorodetskyi, Mykola; Salamatina, Olga (Technology audit and production reserves, 2025)
The object of research is the process of detecting the ignition of materials in a premise based on the joint use of current sample means and variances of the controlled hazardous gas environment parameter. The problem is to develop a method for detecting the ignition of materials based on the joint use of current sample means and variances of the controlled hazardous gas environment parameter in a premise. The synthesis of the optimal method for detecting fires was achieved by moving from the space of controlled hazardous gas environment parameters to the spaces of sample means, sample variances, and also the space of joint sample means and variances. Under conditions of large samples, the distribution of sample means, sample variances and its joint values asymptotically tends to a Gaussian distribution. This allows to use the likelihood ratio criterion, which is optimal, in the synthesis. Unlike the traditional approach, the likelihood ratio is current and is determined for a fixed Gaussian distribution in the case of a reliable absence of ignition. It is established that the optimal method of fire detection based on the joint use of sample means and variances with the same quality indicators outperforms the optimal methods of fire detection based only on the sample mean or sample variance of the controlled hazardous parameter of the gas environment. This is explained by the fact that the optimal method of fire detection based on the joint use of sample means and variances uses a larger amount of information contained in the controlled parameters of the gas environment. The results obtained are useful from a theoretical point of view for the proposed optimal methods of fire detection. The practical significance of the work lies in the further improvement of existing fire protection systems of facilities in order to prevent fires.